Seeds Physiology of Development, Germination and Dormancy, 3rd Edition - Bewley, J. Derek; Bradford, Kent J.; Hilhorst, Henk W.M.; Nonogaki, Hiro.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This updated and much revised third edition of Seeds: Physiology of Development, Germination and Dormancy provides a thorough overview of seed biology and incorporates much of the progress that has been made during the past fifteen years. With an emphasis on placing information in the context of the seed, this new edition includes recent advances in the areas of molecular biology of development and germination, as well as fresh insights into dormancy, ecophysiology, desiccation tolerance, and longevity. Authored by preeminent authorities in the field, this book is an invaluable resource for researchers, teachers, and students interested in the diverse aspects of seed biology.
Structure and Composition -- Development and Maturation -- Synthesis of Storage Reserves -- Germination -- Mobilization of Stored Reserves -- Dormancy and the Control of Germination -- Environmental Regulation of Dormancy and Germination -- Longevity, Storage and Deterioration.
Keywords: Life sciences; Biochemistry; Plant anatomy; Plant breeding; Plant physiology; Life Sciences; Protein Science; Plant Biochemistry; Plant Anatomy/Development.; Plant Physiology; Plant Genetics & Genomics